The gut microbiota as a target to control hyperuricemia pathogenesis: Potential mechanisms and therapeutic strategies - Wang, Jing; Chen, Yong; Zhong, Hao; Chen, Fang; Regenstein, Joe; Hu, Xiaosong; Cai, Luyun; Feng, Fengqin (Critical reviews in food science and nutrition, 2022)
Hyperuricemia (HUA) is a metabolic disorder caused by abnormal uric acid (UA) metabolism, which is a complex physiological process involving multiple organs (liver, kidney, and intestine). Although UA metabolism in the liver and kidneys has been elucidated, only a few studies have focused on the process in the intestine. With our growing knowledge of the effects of gut microorganisms on health, the gut microbiota has been identified as a new target for HUA treatment. In this review, the relationship between HUA and the gut microbiota is elucidated, and anti-hyperuricemia mechanisms targeting the intestine are discussed, such as the promotion of purine and UA catabolism by the gut microbiota, increases in UA excretion by the gut microbiota and its metabolites, regulation of UA absorption or secretion in the intestinal tract by certain transporters, and the intestinal inflammatory response to the gut microbiota. Additionally, probiotics (Bifidobacteria and Lactobacilli) and prebiotics (polyphenols, peptides, and phytochemicals) with UA-lowering effects targeting the intestinal tract are summarized, providing reference and guidance for further research.